I got a "D" in salami - Winkler, Henry, 1945- (New York : Grosset & Dunlap, 2003)
Antics ensue after Hank throws his report card into a meat grinder.
"The world's greatest underachiever."
650
Accelerated Reader AR
Keywords: Report cards -- Fiction; Schools -- Fiction